LEARNERS’ ATTITUDES TOWARDS THE SIMS 4 IN BOOSTING THEIR ENGLISH VOCABULARY MASTERY - Fikri Adzani Hidayatullah; Zaitun (LPPM Universitas PGRI Jombang, 2026)
This study investigates Indonesian learners’ attitudes toward using The Sims 4 to boost English vocabulary mastery, aiming to identify learners’ vocabulary learning challenges and examining how digital simulation games influence motivation and contextual vocabulary acquisition among English as a foreign language learners aged 18–25. The study employed a mixed-method explanatory sequential design, collecting quantitative data from 99 respondents through a Likert-scale questionnaire followed by semi-structured interviews with selected participants. Descriptive statistics and thematic analysis were used to analyze learners’ perceptions, experiences, and challenges related to vocabulary learning through gameplay. The findings reveal that learners generally perceive The Sims 4 as motivating, enjoyable, and effective in supporting contextual and daily-life vocabulary learning, particularly by providing meaningful exposure through simulated real-life activities. Therefore, while The Sims 4 enhances learners’ engagement, motivation, and incidental vocabulary acquisition, it should be used as a supplementary learning tool to boost students’ vocabulary mastery. It is recommended that educators combine digital games with traditional vocabulary teaching strategies to maximize meaningful learning activities.